A review on obesity as a risk factor for mortality in COVID-19 disease - Tenorio-Mucha, Janeth (2020)
This review presents evidence available up to June 2020 dealing with the effects from obesity as a possible factor increasing mortality in patients diagnosed with COVID-19 infection. Quality for most of the studies was good according to the Newcastle Ottawa scale (7/9 or higher). Studies reported follow-up periods between February 6th up to May 17th, 2020. In patients with COVID-19, obesity was a risk factor for mortality. Obese persons should be treated as a highrisk population, and preventive measures against transmission of the aforementioned infection must be intensified, and specialized assistance must be given to confirmed COVID-19 cases.